2023
DOI: 10.1002/cnr2.1871
|View full text |Cite
|
Sign up to set email alerts
|

Bridging racial and ethnic disparities in cancer research

Richa Sharma,
Amit K. Tiwari

Abstract: Bridging racial and ethnic disparities in cancer researchThe issue highlights the need to bridge racial and ethnic disparities in cancer research to promote equitable healthcare outcomes. Our knowledge of unique risk factors and disease progression patterns in minority groups is hindered by underrepresentation of these groups in clinical trials and genomic databases. Thus, personalized treatment strategies cannot be developed effectively. Biological diversity among racial and ethnic groups adds further complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Interest in improving representation in clinical trials has increased the understanding of gender and racial disparities in recruitment and retention of patients in such trials . For example, the US Food and Drug Administration issued draft guidance to the drug development industry for developing plans to enroll more participants from historically underrepresented racial and ethnic groups into clinical trials in the US .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in improving representation in clinical trials has increased the understanding of gender and racial disparities in recruitment and retention of patients in such trials . For example, the US Food and Drug Administration issued draft guidance to the drug development industry for developing plans to enroll more participants from historically underrepresented racial and ethnic groups into clinical trials in the US .…”
Section: Introductionmentioning
confidence: 99%
“…Interest in improving representation in clinical trials has increased the understanding of gender and racial disparities in recruitment and retention of patients in such trials. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 For example, the US Food and Drug Administration issued draft guidance to the drug development industry for developing plans to enroll more participants from historically underrepresented racial and ethnic groups into clinical trials in the US. 11 But efforts to recruit other historically disadvantaged groups, such as individuals with lower income and lower educational attainment, have been lacking despite a recent report that found that these groups are substantially more likely to have a chronic medical condition, such as cardiovascular disease, than those with a higher income and educational level.…”
Section: Introductionmentioning
confidence: 99%